Delimitação de área superficial e monitoramento da qualidade volumétrica da água com sensoriamento remoto - Ferreira, Vítor Augusto (2025)
Water resource monitoring is crucial for environmental management, especially in strategic areas such as the Funil Reservoir, located in Minas Gerais, Brazil. The dam plays a significant role in water supply, power generation and leisure. In this context, assessing water quality is essential to diagnose the environmental status of the reservoir, understand its potential uses and identify pollutants that compro- mise its sustainability. Remote sensing stands out as an efficient and cost-effective tool for analyzing water bodies, allowing the mapping of physical and chemical characteristics and continuous monitoring of these environments. These techniques enable the detection of environmental changes and assist in the integrated management of water resources. The use of remote sensing methodologies makes it possible to create water masks, automatically delimiting water areas in satellite images and facilitating the identification of variations in the coverage and extent of these resources over time. This work proposes the use of advanced remote sen- sing techniques to define water masks and calculate spectral indices relevant to water quality in the Funil Reservoir. The expected results include detailed maps of the dam area, the detection of temporal changes and the generation of data that can support actions aimed at the conservation and sustainable use of this strategic water resource.